2000
DOI: 10.1021/jp002101p
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Vibrational Properties of Thiophene on Si(100)

Abstract: The surface reactions of thiophene on Si(100)-2×1 have been investigated as part of a larger study on the interaction between five-membered heterocyclic aromatic molecules and silicon substrates. Using XPS, UPS, and HREELS, two adsorption states are identified at 120 K, corresponding to physisorbed and chemisorbed thiophene. The former desorbs below 200 K, whereas the latter strongly binds to the surface, showing lower C(1s) and S(2s) binding energies. HREELS reveals that chemisorbed thiophene is a 2,5-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 63 publications
8
56
0
Order By: Relevance
“…Similarly, the S 2s spectra of thiophene showed a feature at 227.4 eV for chemisorbed species at room temperature [254]. Upon surface annealing, further transformations take place based on oxygen and sulfur migration.…”
Section: Heteroaromatics: Aromaticity As a Driving Force In Surface Pmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, the S 2s spectra of thiophene showed a feature at 227.4 eV for chemisorbed species at room temperature [254]. Upon surface annealing, further transformations take place based on oxygen and sulfur migration.…”
Section: Heteroaromatics: Aromaticity As a Driving Force In Surface Pmentioning
confidence: 92%
“…Experimental studies by Qiao et al employed a combination of photoelectron spectroscopy and HREELS to observe the presence of alkane groups in the adsorbate of both furan [238] and thiophene [254] and also to ascribe C 1s XPS peaks observed at 284.7 and 285.5 eV to α-and β-carbon atoms respectively, while O 1s spectra for furan exhibited only one peak at 532.3 eV [238]. Similarly, the S 2s spectra of thiophene showed a feature at 227.4 eV for chemisorbed species at room temperature [254].…”
Section: Heteroaromatics: Aromaticity As a Driving Force In Surface Pmentioning
confidence: 99%
“…Based on low-energy electron diffraction (LEED), Auger electron spectroscopy (AES), and ultraviolet photoelectron spectroscopy (UPS) data, they reported that the C 4 H 4 S molecule was chemisorbed molecularly on the Si(1 0 0) surface by the [2 + 2] cycloaddition mechanism. In contrast to above mentioned results, Qiao et al [14] suggested a [4 + 2] cycloaddition mechanism for the same surface reaction from UPS, XPS, and HREELS studies. The thiophene/ Si(1 0 0)-(2 Â 1) structure have also been theoretically studied by the hybrid density functional (B3LYP) method within a cluster model approach [11].…”
Section: Introductionmentioning
confidence: 89%
“…This rapidly growing field has been considered in a large number of experimental and theoretical investigation so as to elucidate the structural and electronic properties of such systems [4][5][6][7][8]. Among the heterocyclic hydrocarbons, the interaction of the thiophene (C 4 H 4 S) [9][10][11] and furan (C 4 H 4 O) [12][13][14] with the Si(1 0 0) surface has also attracted with a great attention because this organic semiconductor structures is the backbone of the highly ordered thin-film conducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…TPD spectra collected from Au(1 1 1) exposed to OTTP at 298 K in UHV for mass 2 (H 2 , top) and mass 34(H 2 S, bottom) with a heating rate of 2 K/s. whereas thiophene derivatives on Si(1 1 1) and Si(1 0 0) decomposed at room temperature and $450 K, respectively [36], suggesting that thermal decomposition of thiophene derivatives strongly depends on surface properties as well.…”
Section: Methodsmentioning
confidence: 99%